ANALISA KEKUATAN RANGKA PADA DESAIN MESIN PENGAYAK PASIR ROTARI KAPASITAS 10 KG MENGGUNAKAN SIMULASI SOLIDWORK - nalahuddin, Muchlisi; Ihsan, Ainul; Kudus Susalam, Malikil (Jurnal Ilmiah Poli Rekayasa, 2025)
This research discusses the analysis of the rotary system sand sieving machine frame with a capacity of 10 kg using Solidworks 2018 with the Finite Element Analysis (FEA) Method. This research aims to overcome manual problems in the sand sieving process in building construction by developing an efficient and reliable automatic machine. Technology is identified as a basic need of modern society because of its ability to increase efficiency and productivity in various activities. Sand, as an important construction material, must be sieved from rocks and gravel before use. Current manual sieving processes require a lot of effort and time, prompting the need for automated solutions such as the rotary sand sieving machine designed in this research. Machine design focuses on frame strength as the main component that supports operational loads. The frame strength analysis was carried out using Solidworks 2018 with the FEA method to ensure its safety and resistance to a load of 10 kg. The analysis results show that the machine frame can bear operational loads well. The maximum stress that occurs in the frame is 9.248 N/m2, far below the yield strength of the material used. The maximum deformation (displacement) that occurred was 1,058 mm, mainly concentrated in the critical areas analyzed. Safety factor analysis shows that the frame meets safety standards with a safety factor of 2.7, exceeding the expected value for construction industry applications